2003
DOI: 10.1034/j.1600-0714.2003.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying odontogenic cyst: clinicopathological features and immunohistochemical profile of 10 cases

Abstract: Calcifying odontogenic cysts showed odontogenic cytokeratin profile and bcl-2 and Mel-CAM expression indicate that these proteins may be involved in the development of COC. There were no recurrences after surgery, irrespective of their proliferative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
3
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 24 publications
3
42
3
15
Order By: Relevance
“…In the present study, the frequency of calcifying odontogenic cysts (2.8%) was higher than that reported in previous studies in which these lesions accounted for 1.0% or less of all OCs (2,3). In contrast to other reports (2,20), in the present series most cases were diagnosed in women. Regarding anatomic location, our results showed a similar distribution in the mandible and maxilla.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In the present study, the frequency of calcifying odontogenic cysts (2.8%) was higher than that reported in previous studies in which these lesions accounted for 1.0% or less of all OCs (2,3). In contrast to other reports (2,20), in the present series most cases were diagnosed in women. Regarding anatomic location, our results showed a similar distribution in the mandible and maxilla.…”
Section: Discussioncontrasting
confidence: 54%
“…Studies performed in Europe (2) and Chile (3) showed that odontogenic keratocysts accounted for 18.1% and 23.3% of all OCs diagnosed in pediatric populations, respectively. The clinical and histopathologic features of calcifying odontogenic cysts have generated disagreement and confusion regarding their classification and terminology (20). On the basis of the new WHO concept, calcifying odontogenic cysts not only contain a neoplasm but also a cyst (3).…”
Section: Discussionmentioning
confidence: 99%
“…To summarize the data, the review of cases was performed in the following manners: first, the data from reviews carried out in 1991 by Buchner et al [7] were used; to confirm the information, all works described by these authors between 1962 and 1991 [1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] were reviewed. Second, the papers from 1991 to 2010 [5,[22][23][24][25][26] were analyzed. Together with this current case report, a total of 44 acceptable cases of PCOC for evaluation and analysis were selected.…”
Section: Discussionmentioning
confidence: 99%
“…COC represents approximately 5-7% of odontogenic tumors and 1% of all cysts of the jaw (1,6). Most cases (70%) are intraosseous lesions almost equally affecting the maxilla and mandible, with a predilection to the anterior regions (2,6).…”
Section: Discussionmentioning
confidence: 99%
“…Ameloblastomatous proliferating 4. Dentinogenic ghost cell tumor In 1992, the World Health Organization (WHO) classified COC as a neoplasm rather than a cyst, but confirmed that most cases are neoplastic (6). In 1998, Toida suggested a classification that included three main subdivisions of COC: cystic, neoplastic and combined lesions.…”
Section: Introductionmentioning
confidence: 99%